Mapping transgender studies in Portugal: a systematic search and narrative review - Moleiro, C.; Alarcão, V.; Neves, L. R. (Journal of Gender Studies, 2023)
Information on the multiple experiences and heterogeneous diversity of all individuals who self-identify as trans and/or outside of the gender binary is still scarce. A scoping review approach was implemented to identify the nature and extent of research evidence on trans people in Portugal and to contribute to mapping the rapidly changing social, medical, and political landscape of Portuguese trans issues. Findings provided a comprehensive overview of the major issues that have been addressed and of the existing conceptual and methodological frameworks for studying trans individuals while identifying future approaches for studying the diversity of the trans population.